INTEGRO-DIFFERENTIAL PRINCIPLE IN PERSONALITY DEVELOPMENT: THE POSSIBILITY OF MATHEMATICAL DESCRIPTION WITHIN THE STRUCTURAL THEORY FRAMEWORK - Elena V. Slavutskaya; Leonid A. Slavutskii (Russian Journal of Education and Psychology, 2023)
The research is devoted to the mathematical description possibility of the personality development dynamics within the factor models framework. The dynamic Ornstein-Uhlenbeck equation is used, which describes a stochastic stationary process tending to an equilibrium state. This equation has already been used by psychologists to describe the dynamics of development within the framework of personality “Big Five” model. In this paper, this approach is used for qualitative interpretation and visual demonstration of the integration and differentiation principles in personality development based on the transformation of R. Cattell’s factor model. A simple analytical solution of the equation for averaged psychological indicators is compared with the results of the author’s longitudinal study of the dynamics of changes in the personal traits interrelations for schoolchildren in the transition period between primary school and adolescence. When comparing theoretical and experimental results, it is shown that the model makes it possible to assess the patterns of mental development in a transitional (crisis) period, to interpret the mechanism of development, the manifestation of heterochrony and the integro-differentiation principle.